Evidence for gravitactic behaviour in benthic diatoms - Frankenbach, Silja
Vertical migration by diatoms is a well-known phenomenon, occurring in intertidal and subtidal benthic biofilms. It is partially endogenously driven, as cell movements can be observed in the absence of external stimuli such as light, temperature or water cover. Although vertical migration of diatoms under constant conditions has often been attributed to geotactic orientation, this hypothesis has never been experimentally demonstrated. Our study tested the gravitactic nature of the vertical migratory behaviour of benthic diatoms in sedimentary biofilms, using an experimental setup designed to distinguish gravitaxis from surface-oriented cell movements. The hourly variation of surface diatom biomass during migratory cycles was compared in homogenized sediment samples kept facing upwards (surface-oriented and gravity stimuli coinciding; controls) and facing sideways or downwards (surface-oriented and gravity stimuli not coinciding). During the experiments, sediment samples were kept in complete darkness in custom-made, sealed measuring chambers designed to avoid any contact with atmospheric air and the formation of physico-chemical gradients near the surface. Microalgal biomass was monitored non-intrusively using PAM fluorometry, by measuring dark-level fluorescence, F o . The results showed a clear effect of sample orientation in relation to the gravitational stimulus. In the controls, a biphasic pattern in surface biomass was observed, with the formation of a clear biomass peak (three-to six-fold increase) followed by a slower decrease. In contrast, in samples facing sideways or downwards, surface biomass also varied but to a much lesser extent (typically < two-fold). These results strongly suggest that, in the absence of light, upward vertical migration of benthic diatoms is mostly guided by negative gravitaxis, supporting the often hypothesized capacity of these cells to sense and use gravity to move vertically within the sediment.